The long, long trailer [videorecording (DVD)] - Minnelli, Vincente; Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Main, Marjorie, 1890-1975; Wynn, Keenan, 1916-1986; Twiss, Clinton (Warner Home Video, 2006)
Lucy and Desi play newlyweds who hit the honeymoon road with a 40-foot trailer in tow.